(untitled) (Eurasian Journal of Ecology, 2024)
Titanium-magnesium combine in East Kazakhstan region, namely in Ust-Kamenogorsk city is one of the most advanced enterprises in Kazakhstan and one of the leading enterprises in CIS on extraction of raw materials, technique of extraction of metals and quality of the received production. In a view of that in literature there are no materials on biochemical studying of reaction of an organism to occupational stress we executed work, namely experiment on animals with inhalation introduction of a dust of a titanium slag. To study the indices of blood nitrogen exchange and oxyproline excretion under the action of one of the main adverse factors, the dust factor on the body of laboratory animals. The experiment was carried out by introducing titanium slag dust, and control animals were injected with physiological solution. Assessment of the indices of nitrogenous metabolism in blood, was determined by such indicators as urea, residual nitrogen, creatinine, the content of oxyproline in daily urine, as well as cyto-morphological studies of internal organs. As a result of the experiment, the unidirectional changes of blood nitrogen and urinary oxyproline parameters with cytomorphological changes in the kidneys were revealed. Key words: titanium-magnesium production, laboratory animals, indicators of blood nitrogen metabolism, oxiproline and cyto-morphological data.